(untitled) (Progress Annals: Journal of Progressive Research, 2024)
This article provides information on the characteristics of suicide in adolescence and measures to prevent it . Also, the important aspects of carrying out correctional educational work with teenagers with a high level of suicidal risk are covered in detail.